Combating low completion rates in Nordic welfare states: policy design in Norway and Sweden. Issue 3 (3rd July 2019) - Helgøy, Ingrid; Homme, Anne; Lundahl, Lisbeth; Rönnberg, Linda
ABSTRACT: Low completion rate in upper secondary education is seen as a big problem in the Nordic countries. School failure has shown to dramatically increase the risks for unemployment and labour market exclusion with severe consequences for both society and the young person. This paper analyses national policy measures to combat low upper secondary education completion rates in Norway and Sweden, often regarded as representing a social democratic welfare model and a universalistic transition regime. The analysis demonstrates that although this issue has received extensive political attention, the two countries display somewhat different policy designs. The Norwegian approach is proactive and targeted while the Swedish policy is more general and directed towards reforming organisational structures in upper-secondary education. In sum, our analysis demonstrates that national governance structures shape and influence policy design in the context of an increasingly diversified Nordic social democratic welfare state regime.